The response of rumen pH, fermentation parameters and rumen bacteria to feeds of different concentrate to roughage ratios in buffalos - Wang, Rongjiao; He, Shichun; Huang, Dan; Wu, Dongwang; Peng, Hongen; He, Shaoying; Guo, Taiqing; Chen, Tao; Fu, Xianhai; Chen, Changguo; Jiaka, Latie; He, Min; et al. (Frontiers in Microbiomes, 2023)
This experiment was conducted to study the regularity influence in apparent digestibility, rumen fermentation parameters, and relative bacterial abundance in buffaloes with different concentrate to roughage ratios. Three adult female barren buffaloes with permanent rumen fistulas were fed five diets with concentrate to roughage ratios of 20:80, 35:65, 50:50, 65:35, and 80:20 according to an incomplete Latin square design of 3×5, respectively. The pre-feeding period of each period was 12 d. From day 13 to 15 of the experiment, the feed intake of each buffalo was accurately recorded and all feces were collected. Samples of diet and feces were collected for nutrient analysis. Rumen fluid was collected to determine rumen fermentation parameters, and rumen bacteria were analyzed by 16S rRNA sequencing. After 2 hours of feeding in the morning on the 15th day of the experiment, rumen bacteria were analyzed. The daily gain and DMI (G/kgW0.75) reached the highest at the concentrate to roughage ratio of 50:50, and the apparent digestibility of ADF NDF NDICP ADICP reached the highest at the concentrate to roughage ratio of 35:65. The weight loss of the experimental animals when the concentrate to roughage was 80:20. Rumen pH decreased with the increase of concentrate level, starch content and NFC content. The rumen ammonia nitrogen concentration increased with the increase in the concentrate to roughage ratio and protein content. The concentration of total volatile fatty acids (mmol/L) in the rumen decreased with the increase of NDF but increased with the increase of NFC and CP, and the acetic acid proportion increased with the increase of NDF. There were differences in the relative abundance of rumen bacterial microbiota with the different concentrate to roughage ratios. Moreover, the relative abundance of each bacterial microbiota changed regularly with the change of concentrate to roughage ratio. The relative abundance of Bacteroidetes, Firmicutes, and other rumen core microbiota varied linearly or nonlinearly with the change of concentrate to roughage ratio. This suggests that the relative abundance of the ratio of rumen microbiota can be used to specify or measure rumen health and subacute rumen acidosis/rumen acidosis.